(3JWhQ GdfXGe GdYbGHj GdeUQj aj YgO eMeO Ydj (B/ s - (3MSjf Rcj YHO GddWjas; (3Uhaj CHh WGdHs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1998)
(3JfGhdJ GdOQGSI ehVhY GdfXGe GdYbGQi GdeUQi ai YgO eMeO Ydi hNdaGFg heGONd Ydjg ef JWhQ efP Jhdi eMeO Ydi ebGdjO GdCehQ MJi UOhQ GdJbfjfGJ GdCgdjI SfI (B1883 (3e , ceG JfGhd eUGOQ GdfXGe GdYbGHi ai eUQ ai aJQI Mce eMeO Ydi hNdaGFg MJi UOhQ bGfhf GdYbhHGJ GdCgdi , hJfGhdJ CjVG LgGJ GdbVGA GdLfGFi GdeUQi ai YgO eMeO Ydi hNdaGFg hGdCMcGe GdYGeI ai GdJLQje hGdYbGH ai YgO eMeO Ydi hNdaGFg hGdLQGFe hJWhQ GdYbGH YdjgG ai YgOg hbO fhbTJ GdfJGFL(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe adSaI GdbGfhf hJGQjNg, (B1998. s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B489-505.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3eMeO Ydj HGTGs; (3adSaI GdbGfhf hJGQjNIs; (3eUGOQ GdfXGe GdYbGHjs; (3GdbVGA GdLfGFj GdeUQjs; (3GdbVGA GdTQYjs; (3GdeLGdS GdbVGFjIs; (3GdbVGA GdbfUdj aj eUQ s; (3GdYbhHGJ GdeGSI HGdMjGIs; (3GdYbhHGJ GdSGdHI ddMQjIs; (3GdEQSGd Gdj GdLgGOjIs; (3LQGFe GdMOhOs; (3LQjeI GdRfGs; (3LQjeg bWY GdWQjbs; (3LQGFe GdbUGUs; (3LQGFe GdRQGYIs; (3LQGFe GdEYJOGA Ydi eG Ohf GdfaSs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3adSaI GdbGfhf hJGQjNIs